2020
DOI: 10.1108/et-05-2020-0141
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical innovation in higher education and active learning methodologies – a case study

Abstract: PurposeThe aim of this study is to obtain a broader knowledge of innovative pedagogical practices in higher education, by analysing the particular case of the Higher Institute of Administration and Languages (ISAL). The literature review reveals a gap in this scientific field, and filling this gap is as imperative as the need to articulate higher education with the Students' Profile by the End of Compulsory Schooling.Design/methodology/approachThis research adopts a qualitative methodological approach, in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…From the observation of the youth club in Tokyo, it has been found that ESD-related activities conducted at a community centre can be a trigger for nurturing university students’ capability and leadership through team-learning in the context of ESD. This outcome is supported by discussions presented by [ 31 ], who suggested that it has been critical to focus higher education on enhanced students’ critical thinking and ideas in the context of contributing to communities. Educational institutions such as universities should be encouraged to develop partnerships with multi-sectoral stakeholders in the context of ESD.…”
Section: Methodsmentioning
confidence: 57%
“…From the observation of the youth club in Tokyo, it has been found that ESD-related activities conducted at a community centre can be a trigger for nurturing university students’ capability and leadership through team-learning in the context of ESD. This outcome is supported by discussions presented by [ 31 ], who suggested that it has been critical to focus higher education on enhanced students’ critical thinking and ideas in the context of contributing to communities. Educational institutions such as universities should be encouraged to develop partnerships with multi-sectoral stakeholders in the context of ESD.…”
Section: Methodsmentioning
confidence: 57%
“…The uniform practice as revealed by the Executive Deans/Deans is that training is provided steadily in all the universities across the nation. This is unlike the experience of universities in other African countries and beyond [80,81,82,30,83]. It is noteworthy that the Faculty of Education and the Faculty Health Sciences excelled (100%) all others in training staff members because of certain peculiarities.…”
Section: Training Of Staff Members To Work On (Operate) the Newly Acq...mentioning
confidence: 80%
“…This practice is exceptional and commendable in South African context considering the speed of change from the traditional system of teaching to complete online teaching and learning. This is impressive because pedagogy has been a major global challenge while implementing technologies for teaching in universities [80,33,84,81,85,86,87,28,22,16]. In addition, a vast majority of Health Sciences graduates deal with human lives.…”
Section: Training Of Staff Members To Work On (Operate) the Newly Acq...mentioning
confidence: 99%
“…Portuguese researchers, based on modern educational approaches such as a focus on practice and development of students' creativity, critical thinking, readiness for group work, and improvement of communication skills, have identified such pedagogical innovations as differentiated learning, collaboration, problem-based and problem-solving learning, role play, blended learning, and flipped classroom (Carvalho et al, 2021). In this context, the issue of teacher cooperation and the exchange of experience directly related to the use of pedagogical innovations when working with students is critically important.…”
Section: Literature Reviewmentioning
confidence: 99%